Primary lymphomas of the genitourinary tract: A population-based study - Palumbo, Carlotta (Asian J Urol, 2020)
OBJECTIVE: We performed a population-based analysis focusing on primary extranodal lymphoma of either testis, kidney, bladder or prostate (PGUL). METHODS: We identified all cases of localized testis, renal, bladder and prostate primary lymphomas (PL) versus primary testis, kidney, bladder and prostate cancers within the Surveillance, Epidemiology, and End Results database (1998–2015). Estimated annual proportion change methodology (EAPC), multivariable logistic regression models, cumulative incidence plots and multivariable competing risks regression models were used. RESULTS: The rates of testis-PL, renal-PL, bladder-PL and prostate-PL were 3.04%, 0.22%, 0.18% and 0.01%, respectively. Patients with PGUL were older and more frequently Caucasian. Annual rates significantly decreased for renal-PL (EAPC: −5.6%; p=0.004) and prostate-PL (EAPC: −3.6%; p=0.03). In multivariable logistic regression models, older ager independently predicted testis-PL (odds ratio [OR]: 16.4; p<0.001) and renal-PL (OR: 3.5; p<0.001), while female gender independently predicted bladder-PL (OR: 5.5; p<0.001). In surgically treated patients, cumulative incidence plots showed significantly higher 10-year cancer-specific mortality (CSM) rates for testis-PL, renal-PL and prostate-PL versus their primary genitourinary tumors. In multivariable competing risks regression models, only testis-PL (hazard ratio [HR]: 16.7; p<0.001) and renal-PL (HR: 2.52; p<0.001) independently predicted higher CSM rates. CONCLUSION: PGUL rates are extremely low and on the decrease in kidney and prostate but stable in testis and bladder. Relative to primary genitourinary tumors, PGUL are associated with worse CSM for testis-PL and renal-PL but not for bladder-PL and prostate-PL, even after adjustment for other-cause mortality.